CRISPR screens identify tumor‐promoting genes conferring melanoma cell plasticity and resistance. Issue 5 (16th March 2021) - Gautron, Arthur; Bachelot, Laura; Aubry, Marc; Leclerc, Delphine; Quéméner, Anaïs M; Corre, Sébastien; Rambow, Florian; Paris, Anaïs; Tardif, Nina; Leclair, Héloïse M; Marin‐Bejar, Oskar; Coulouarn, Cédric; et al.
Abstract: Most genetic alterations that drive melanoma development and resistance to targeted therapy have been uncovered. In contrast, and despite their increasingly recognized contribution, little is known about the non‐genetic mechanisms that drive these processes. Here, we performed in vivo gain‐of‐function CRISPR screens and identified SMAD3, BIRC3, and SLC9A5 as key actors of BRAFi resistance. We show that their expression levels increase during acquisition of BRAFi resistance and remain high in persister cells and during relapse. The upregulation of the SMAD3 transcriptional activity (SMAD3‐signature) promotes a mesenchymal‐like phenotype and BRAFi resistance by acting as an upstream transcriptional regulator of potent BRAFi‐resistance genes such as EGFR and AXL. This SMAD3‐signature predicts resistance to both current melanoma therapies in different cohorts. Critically, chemical inhibition of SMAD3 may constitute amenable target for melanoma since it efficiently abrogates persister cells survival. Interestingly, decrease of SMAD3 activity can also be reached by inhibiting the Aryl hydrocarbon Receptor (AhR), another druggable transcription factor governing SMAD3 expression level. Our work highlights novel drug vulnerabilities that can be exploited to develop long‐lasting antimelanoma therapies. Synopsis: Using a CRISPR activation screening, we identified genes involved in BRAF inhibitor (BRAFi) resistance in cutaneous melanoma. Their upregulation promoted tumour growth of therapy‐naïve melanoma cells and BRAFi‐resistance. Inhibition of these genes (not mutated) may be useful for therapy. Gene up‐regulation obtained by CRISPR activation identified new targets for cutaneous melanoma. AhR‐SMAD3 axis promoted BRAFi‐resistance and cell plasticity. The SMAD3‐signature was found in most BRAFi‐resistant human melanoma tumours. Inhibition of SMAD3 alone or in combination with BRAFi impaired survival of BRAFi‐resistant cells. Abstract : Using a CRISPR activation screening, we identified genes involved in BRAF inhibitor (BRAFi) resistance in cutaneous melanoma. Their upregulation promoted tumour growth of therapy‐naïve melanoma cells and BRAFi‐resistance. Inhibition of these genes (not mutated) may be useful for therapy.